Anthropogenic change of landscapes due to amber extraction and measures for their restoration - Koshel, A.; Kolhanova, I.; Kempa, O. (Land Management, Cadastre and Land Monitoring, 2025)
This research article discusses the problems of anthropogenic landscape change as a result of amber extraction and substantiates measures to restore them. Amber extraction is an important economic process, but it causes significant disruption to natural ecosystems and landscapes. Uncontrolled extraction leads to soil degradation, landform changes, loss of biodiversity and disruption of the hydrological regime of the territories.The article presents an analysis of the environmental consequences of illegal amber extraction and its impact on the landscapes of Polissia. In particular, the process of quarrying, destruction of vegetation and formation of new erosive landforms is considered.The article considers the aspects of detecting changes in the landscape of the studied territory using Sentinel multispectral satellite images of medium spatial resolution in the dynamics of time periods. The cost of restoration of disturbed lands in the model territory by means of reclamation of disturbed lands is calculated.Based on the analysis, a set of measures for reclamation of disturbed territories is proposed. The main focus is on ecological restoration of land through reclamation, planting of autochthonous plant species and restoration of the natural water balance. The importance of scientifically sound planning of reclamation works to ensure the sustainability of natural ecosystems in the post-mining period is also substantiated.The developed recommendations are aimed at ensuring sustainable development of the region by restoring natural landscapes and improving the environmental situation. Implementation of the proposed measures will help minimise the negative impacts of amber mining and ensure the rational use of land resources in the future.Key words: land protection, land management, land reclamation, land management, land improvement, amber mining.
Keywords: land protection; land management; land reclamation; land improvement, amber mining